LEGAL PROTECTION AGAINST THE REVENGE PORN VICTIMS - Wishinta, Anisya Yudistya; Suroso, Imam (jfpublisher, 2022)
People's needs in getting information become easier in the modern era. It is due to Indonesian digital-based information and communication technology every day increasing from the user and technology aspects. Cybercrime can be interpreted as one of the worst parts of technology and communication developments that have a very negative impact on the community. In all areas of modern life today, it can have positive and negative impacts on users. Revenge-motivated pornography is a cybercrime committed by adjusting pornographic material without the victim's consent with the motive of revenge. Thus, the victim suffers or is mentally injured, then full protection starts from the right to treatment, the right to protection, and the right to recovery. This research used a normative type of research combined with library research. The objective of this research is to analyze the legal protection for the victims of revenge porn. It is provided by the government as stated in the relevant legislation which is very necessary for the victim.